A Prophetic Pastoral of Presence: An “Exchange of Places.” Re-contextualizing the Encounter of Jesus and the Leper in Mark 1:40-45 for the Role of the Asian Church in the Midst of Pandemic Covid-19 - Gregorius Tri Wardoyo; Yosafat Roni Sentosa (Asosiasi Ahli Filsafat Keilahian Indonesia, 2021)
The pandemic due to covid-19 makes the Asian Church stuttering in their services especially to the patients of covid-19. In light of Mark 1:40-45, the author proposes to the Asian Church to do a prophetic pastoral presence, just say it an “exchange of places” as it is done by Jesus who takes the place of the leper as a risk of His action. To arrive at such conclusion, the author proceeds this study by analysing the text of Mark 1:40-45 from the narrative perspective and intertextual approach, then the reader is invited to review the consciousness of the FABC regarding its basis and praxis in Asia and how the Asian Church is trying to bring the face of God for the Asian people.